DOP15 Clinical relevance of endoscopic peri-appendiceal red patch in Ulcerative Colitis patients. (27th May 2021) - Reijntjes, M; Heuthorst, L; Gecse, K; Mookhoek, A; Bemelman, W; Buskens, C
Abstract: Background: Recently, increasing evidence is suggesting appendectomy as an alternative treatment approach for ulcerative colitis (UC), especially in case of pathological inflammation of the appendix. Therefore, pre-operative identification of appendiceal inflammation could be of clinical importance to predict efficacy of therapeutic appendectomy. This study assessed the incidence of peri-appendiceal red patch (PARP) on colonoscopy, with the aim to correlate PARP to patient and disease characteristics. In addition, the prognostic relevance of PARP on course of disease, and more specifically, histopathological findings of inflammation in resection specimens of the appendix were assessed, to analyze if PARP could potentially be used to identify patients eligible for appendectomy. Methods: All consecutive patients with UC undergoing colonoscopy in 2014 or 2015 were included to determine the incidence of PARP in a cross-sectional study. Findings were correlated to patient and disease characteristics, upscaling of treatment during disease course and colectomy rates. Degree of inflammation of the appendix in case of subsequent appendectomy/colectomy was determined and results were compared between patients with and without PARP. Histological inflammation was scored by an independent pathologist using the Robarts histopathology index (RHI). Results: In total, 249 patients with an eligible endoscopy report were included. The incidence of PARP was 17.7% (44/249). Patients with PARP were significantly younger and had a shorter disease course. PARP patients with active disease had proctitis more frequently, although not significant (29.4% vs 11.4%, p= 0.19). Out of 44 PARP patients, 27 (61.4%) were found in colonoscopies showing endoscopic Mayo score 0 or 1. Patients with PARP required significantly more upscaling of medical therapy (81.8% vs 58.0%, p= 0.03), and during the median follow up of 71 months the PARP patient group underwent colectomy more frequently (13.6% vs 4.9%, p=0.04). Eighteen appendices were available for histological analysis, of which 8 showed a PARP pre-operatively. Patients with PARP had a higher median Robarts Histology Index (RHI) score compared to patients without a PARP (13.5 vs 6.5 p< 0.01). Conclusion: PARP was predominantly found in UC patients with younger age and shorter disease duration and were demonstrated to have a more severe course of UC. Patients with PARP had a higher histopathological inflammation score. Since pathological inflammation of the appendix has been associated with improved efficacy of therapeutic appendectomy, it could be attractive to analyze if the presence of PARP might help in selecting patients more likely to respond to therapeutic appendectomy.